Engineering surface ligands of nanocrystals to design high performance strain sensor arrays through solution processes. Issue 9 (22nd February 2017) - Lee, S.-W.; Joh, H.; Seong, M.; Lee, W. S.; Choi, J.-H.; Oh, S. J.
Abstract : We demonstrate solution processed and nanocrystal based wearable strain sensor arrays with high sensitivity and stability. Abstract : We demonstrate solution-processed strain sensor arrays using a single material of silver nanocrystals (Ag NCs). We investigate the effect of various ligand treatments on the electromechanical properties of Ag NC thin films. We successfully show that Ag NCs are chemically transformed into (i) highly conductive electrodes through inorganic treatments, exhibiting higher electromechanical stability when compared to vacuum deposited electrodes or commercial silver paste, and (ii) strain-sensitive layers through organic ligand treatments. To further enhance the sensor performance, we introduce a controllable way to form nanocracks only in the organic ligand-treated Ag NC thin film sensing layers. Through ligand exchange processes and the selective nanocrack formation strategy, we dramatically change the electromechanical properties of Ag NC thin films and achieve high gauge factors up to 312 in the sensing layers and low gauge factors down to 0.6 in the electrodes of our optimized devices. Finally, we for the first time develop a simple, low-cost and solution based orthogonal process to integrate Ag NC based strain sensing elements, Ag NC thin film electrodes and solution-processed insulating layers to construct a 4 × 4 multi array sensor architecture. Our wearable multi-array strain sensor systems are used to detect human wrist motion, and reconstruct the shape of the human arm. We believe our solution-processed, high-performance multi sensor arrays can be potentially used in various fields such as electronic skins.